Carbon reduction and commercial leases in the UK - Bright, S (Emerald Group Publishing Limited, 2010)
Purpose – The paper aims to explore the potential impact that the introduction of the UK's carbon reduction commitment (CRC) energy efficiency scheme will have on: energy use in the tenanted commercial built environment; and the idea of the net lease. Design/methodology/approach – The paper reviews various background documents preceding the implementation of CRC in order to identify the abatement incentives established. The common structure of commercial leases and the early property market reaction to CRC are also considered in order to explore how effective the CRC scheme is likely to be in achieving the twin goals of carbon saving and landlord-tenant collaboration. Findings – Key to the success of the CRC scheme will be the way in which the financial and reputational drivers established by the CRC scheme incentivise landlords and tenants to make technological and social changes to reduce energy consumption. Given the variety of ways that energy is supplied to tenanted commercial property, the complexity of the CRC scheme, the traditionally adversarial relations between landlords and tenants and the “split-incentive” of commercial leases, energy abatement opportunities are found to be significantly more limited in the leasehold context than for owner-occupied properties. Nonetheless, the paper notes that the introduction of the CRC scheme has begun an important conversation and is an important step towards tackling energy efficiency. Originality/value – The paper brings together understandings of the legal framework of commercial leases, of the property market and practice, and the landlord and tenant relationship – to consider how the CRC scheme will help to deliver the UK's goal of reducing carbon emissions.